Family control and investors' reactions to acquisition announcements - Teo, James (Nanyang Technological University, 2012)
This study investigates the effects of family control on investors’ reactions to acquisitions. It also examines whether this association is influenced by signals of corporate governance such as CEO-Duality on Board, proportion of independent directors in the firm, proportion of institutional owners and amount of interested party transactions. We tracked and examined 196 acquisition announcements made by family firms listed in the SGX from the year 2005 to 2009. Two regression analyses were done using one independent dummy variable (Two or more family members on Board) and another continuous variable (Proportion of family members on Board). After analyzing both sets of data, we obtained similar results and found that acquiring firms experienced an average positive return. Our results showed that there is no significant relationship between family-controlled firms and investors’ reactions to acquisition announcements. This relationship is positively moderated by higher proportions of independent directors and institutional ownership. A higher amount of interested party transactions within the family firm negatively moderates the relationship. However, duality is found to have no moderating effect. In line with our theoretical predictions, most signals of corporate governance are significant moderators, which suggest that good corporate governance is important for family firms.